2019
DOI: 10.33584/jnzg.2019.81.382
|View full text |Cite
|
Sign up to set email alerts
|

Improving environmental benefits of white clover through condensed tannin expression

Abstract: Forage legumes improve both the intake and quality of the diet in pasture-based livestock systems. However, the high protein content of these forages can lead to inefficient nitrogen utilisation in the rumen and to high nitrogen (N) losses in urine and dung. Condensed tannins in forages have been shown to significantly reduce N leaching and also methane emissions. The use of classical breeding approaches over more than 50 years has failed to elevate condensed tannins in forage legumes. However, molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…However, increase in floral PA concentration and higher flower density led to a decrease in white clover persistence and agronomic performance in the fields. The results from that study suggested that future research should focus on modulating PA expression in white clover leaves, which can concomitantly maintain their agronomic performance in the field. , …”
Section: Discussionmentioning
confidence: 94%
“…However, increase in floral PA concentration and higher flower density led to a decrease in white clover persistence and agronomic performance in the fields. The results from that study suggested that future research should focus on modulating PA expression in white clover leaves, which can concomitantly maintain their agronomic performance in the field. , …”
Section: Discussionmentioning
confidence: 94%
“…Progenies of genetically engineered white clover containing a TaMYB14‐1 transcription factor from Trifolium arvense (Hancock et al, 2012) were produced in another study as described by Roldan et al (2022) and Woodfield et al (2019). Briefly, agrobacterium‐mediated transformation was used to transfer the binary vector into the commercial white clover cultivar Mainstay.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017 seed from backcrosses (BC 1 ) between a transgenic parent and a cultivar Mainstay genotype (2 families each for CTB and CTG event and 1 family for CTF) were grown. In 2018, the BC 2 & T 2 progeny from backcrosses (BC 2 ) (1 each of CTB, CTF and CTG) and T 2 (1 each of CTB & CTG) families were grown (Woodfield et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In legumes, the aim to deliver condensed tannin expression in leaves of white clover and lucerne has been achieved through using a single gene transformation (Hancock et al 2012(Hancock et al , 2014. Condensed tannins in forages, through binding protein, can significantly reduce N leaching and also methane emissions (Woodfield et al 2019). A scenario for achieving co-existence of genetically modified (GM) and non-GM crops and pastures has been proposed to stimulate discussion (Rolleston 2016).…”
Section: Transgenic Technologiesmentioning
confidence: 99%